MEASURING MONEY LAUNDERING USING “THE WALKER GRAVITY MODEL” - ENE, Corina Maria (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Addressing money laundering in terms of measurement possibilities of its dynamics and size is a relatively recent concern. The hidden nature of this phenomenon (money laundering can’t be directly observed) make it impossible to obtain a comprehensive estimate of its size and growth rate. This situation has been widely discussed in economic literature, which has exposed a number of illegal economic transactions measurement methods. Unfortunately, many case studies, econometric variables, or some other techniques used to measure shadow economy are tending to underestimate or overestimate money laundering. Moreover, estimating the size and volume of financial resources generated by organized crime is an extremely difficult task mainly due to lack of appropriate data. Therefore, all existing estimates contain considerable errors and they are only preliminary scientific estimates. Since the official statistics are not able to capture the dynamics of illicit financial flows, the researchers have developed a number of estimation methods. These include "hot money" method, World Bank residual method, the model based on international market prices, the Walker Gravity model, and many similar. The model presented in this paper is the gravity model that makes possible to estimate the illicit funds flow from some jurisdictions to others. Developed in 1994 the method is permanently updating. We try to prove that Walker Model estimates are compatible with nowadays findings on money laundering. Once it knows the money laundering level, one can quantify its economic effect, the impact of money laundering prevention rules, and transnational crimes.